Pastoralist livelihoods and wildlife revenues in East Africa: a case for coexistence? - Homewood, Katherine M.; Chenevix Trench, Pippa; Brockington, Daniel; (Frontiers Media, 2012)
East African arid and semi-arid lands are home to many of the world's pastoralists and most spectacular savanna wildlife populations, attracting substantial conservation and tourism revenues. Yet these peoples are among the poorest (and most affected by extreme climatic events), and the wildlife is in unsustainable decline. National governments, international donors and conservation agencies favour win-win solutions through conservation with development. Maasailand is a hotspot of conservation, poverty and new initiatives to redistribute tourist income. We outline pastoralist livelihoods and how these are changing, then summarise status and trends of wildlife populations, tourism revenues, and conservation and development initiatives in East Africa and Maasailand. We ask to what extent wildlife revenues contribute to pastoralist livelihoods and whether this translates into a robust basis for coexistence. To put in context the role and importance of wildlife- and tourism-based activities, we outline findings from a multi-site study of Maasai livelihoods. Livestock contribute half or more of the mean annual income in all sites, with off-farm work and farming ranking second and third, respectively, except in Mara, where wildlife-based income contributes around 20% income across all wealth categories. In most sites, significant areas have been set aside for conservation and tourism, but wildlife contributes <5% income to a small proportion of households at most. Few wildlife-derived benefits flow to pastoralists, while conservation restrictions constrain production and coping strategies, undermining potential for coexistence. In exceptional circumstances, significant wildlife revenue may reach households, but full social and ecological implications of associated conservancy agreements remain unclear.